Morphological and molecular evidence for a new species from China: Dendrobium zhenghuoense (Epidendroideae; Orchidaceae) - Chen, Shi-Pin; Ma, Liang; Lan, Si-Ren; Li, Ming-He (Phytotaxa, 2016)
We conducted morphological and molecular analyses to describe a new species of orchid, Dendrobium zhenghuoense, which was observed in northern Fujian Province, China. Detailed morphological comparisons between the newly discovered orchid and other members of Dendrobium indicate that D. zhenghuoense is similar to D. luoi, but it can be distinguished by its shorter peduncle, longer lip, pedicel & ovary, as well as the size of its mentum. Molecular analyses based on the ITS of the nuclear ribosomal and plastid DNA (rbcL, matK-trnK, trnH-psbA and trnL-F) support the claims that D. zhenghuoense is a new species in sect. Dendrobium and is genetically similar to D. luoi and D. leptocladum.